Serotonin 5‐HT7 receptor increases the density of dendritic spines and facilitates synaptogenesis in forebrain neurons. Issue 5 (24th March 2017) - Speranza, Luisa; Labus, Josephine; Volpicelli, Floriana; Guseva, Daria; Lacivita, Enza; Leopoldo, Marcello; Bellenchi, Gian Carlo; di Porzio, Umberto; Bijata, Monika; Perrone‐Capano, Carla; Ponimaskin, Evgeni
Abstract: Precise control of dendritic spine density and synapse formation is critical for normal and pathological brain functions. Therefore, signaling pathways influencing dendrite outgrowth and remodeling remain a subject of extensive investigations. Here, we report that prolonged activation of the serotonin 5‐HT7 receptor (5‐HT7R) with selective agonist LP‐211 promotes formation of dendritic spines and facilitates synaptogenesis in postnatal cortical and striatal neurons. Critical role of 5‐HT7R in neuronal morphogenesis was confirmed by analysis of neurons isolated from 5‐HT7R‐deficient mice and by pharmacological inactivation of the receptor. Acute activation of 5‐HT7R results in pronounced neurite elongation in postnatal striatal and cortical neurons, thus extending previous data on the morphogenic role of 5‐HT7R in embryonic and hippocampal neurons. We also observed decreased number of spines in neurons with either genetically (i.e. 5‐HT7R‐knock‐out) or pharmacologically (i.e. antagonist treatment) blocked 5‐HT7R, suggesting that constitutive 5‐HT7R activity is critically involved in the spinogenesis. Moreover, cyclin‐dependent kinase 5 and small GTPase Cdc42 were identified as important downstream effectors mediating morphogenic effects of 5‐HT7R in neurons. Altogether, our data suggest that the 5‐HT7R‐mediated structural reorganization during the postnatal development might have a crucial role for the development and plasticity of forebrain areas such as cortex and striatum, and thereby can be implicated in regulation of the higher cognitive functions. Read the Editorial Highlight for this article onpage 644 . Abstract : Serotonin 5‐HT7 receptor (5‐HT7R) promotes formation of dendritic spines and facilitates synaptogenesis in postnatal cortical and striatal neurons. These morphogenic effects are mediated by cyclin‐dependent kinase 5 (Cdk5) and small GTPase Cdc42. Thus, 5‐HT7R‐mediated structural reorganization during the postnatal development might have a crucial role for the development and plasticity of forebrain areas, and thereby can be implicated in regulation of the higher cognitive functions. Read the Editorial Highlight for this article onpage 644 .